Implementasi Kato Nan Ampek Untuk Meningkatkan Sopan Santun Siswa Melalui Layanan Dasar Bimbingan dan Konseling - Saputri, Sandra Sari; Silvianetri, Silvianetri (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2025)
Abstract: Many students have forgotten the importance of kato nan ampek as a manners of communicating to others. The rapid influence of technology causes students to communicate with words and language that are often heard on social media where this affects the way students communicate.  Kato nan ampek culture needs to be preserved in Minangkabau as a basis for communication to encourage students' polite behavior both to friends, teachers, parents and society. The purpose of this study is to improve students' polite behavior through the implementation of kato nan ampek through basic Guidance and Counseling services. This research was conducted on seventh grade students totaling 32 people. This research method is a class action research conducted in two cycles. The results of this study in cycle 1 students' manners increased by 10.5% and the second cycle increased by 11%. Students' manners are in the good category.Keywords: kato nan ampek; manners; basic service